#TITLE_ALTERNATIVE# - HARDINI (NIM. 101 06 096); Pembimbing Tugas Akhir : Dumaria R. Tampubolon, PhD, DINI
In this …nal project, the determination of the risk premium of an inpatient health insurance, with study case on female patients, is discussed. The data analyzed consists of three variables: number of claims; length of stay (in days); and amount of claims for medicine and laboratory. After the data is “cleaned”, parametric models are selected to represent each variable. The modeling consists of three stages: model selection, parameter estimation and goodness-of-…t test. The probability distributions of total length of stay and of total claims for medicine and laboratory are determined using recursive method and by simulation. The simulation is carried out using MonteCarlo simulation. Using the result from the simulation, the risk premium is then determined using standard deviation principle.